Financing Strategy and Carbon Emission Abatement in a Supply Chain considering Retailers’ Competition - Man Yu; Tuo Li; Zhanwen Shi (Discrete Dynamics in Nature and Society)
This paper investigates the issues of financing channels (bank credit financing, trade credit financing, and dual-channel financing) and carbon emission abatement in a supply chain consisting of one capital-constrained manufacturer and two capital-constrained retailers. Compared with bank credit, we find that every member can make more profit under trade credit when only one financing channel is available. When both bank credit and trade credit are available, the retailers’ financing strategy highly depends on the interest rates charged by the creditors. In addition, we also examine the impact of financing channels on emission abatement. It shows that the manufacturer reduces more carbon emissions under trade credit. Interestingly, the emission abatement has nothing to do with trade credit interest rate when retailers only adopt trade credit, whereas it is closely related to trade credit interest rate under dual-channel financing.